Persepsi Risiko di Indonesia: Tinjauan Kualitatif Sistematik - Aquilina Tanti Arin (Buletin Psikologi, 2012)
The Method of synthesis was narrative subjective review or qualitative review. 40 papers werecollected by searching online papers through Google with key words, but only 26 papers thatincluded in inclusion criteria were used to this study. The result showed that studies about riskperception were conducted in 6 fields, including health, disaster, traffic, sport, environment andtourism. Subjects were varied from children to adult. There were 3 main themes of risk perceptionstudies: first, the relationship between risk perception and behavior; second, factors of riskperception, and third, description of risk perception. Result of this study was discussed to identifygaps of studies about risk perception of Indonesian population for practical consequences in riskmanagement.